2020
DOI: 10.1007/s10633-019-09745-z
|View full text |Cite
|
Sign up to set email alerts
|

Late presentation of RPE65 retinopathy in three siblings

Abstract: Purpose Gene therapy for RPE65 retinopathy has been recently approved. The purpose of this study was to assess retinal structure and function in 3 siblings presenting with late-stage RPE65 retinopathy and to assess the unmet need for such therapy in Saudi Arabia. Methods Search of the retinal dystrophy registry at King Khaled Eye Specialist Hospital and clinical examination including multimodal retinal imaging, full-field electroretinography (ERG), dark adapted Electronic supplementary material The online vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
(24 reference statements)
2
10
0
Order By: Relevance
“…Although the latter was previously described as a hypomorphic allele, associated with low but substantial levels of both RPE65 and 11-cis-retinal in a murine model, 75 we observed a severe phenotype in two unrelated patients (P5 and P19) homozygous for this variant, who had a clinical diagnosis of LCA, nystagmus, keratoconus, light perception, and nondetectable ERG at the study baseline (at 32 and 43 years, respectively). Their clinical presentation was quite similar to the three siblings, homozygous for the same variant, recently described by Magliyah et al, 22 who reported nystagmus and nondetectable ERG in all the siblings and light perception in two patients (at the age of 32 and 36 years), whereas the third cases had a slightly better visual acuity (20/100 at 34 years). Finally, the two patients diagnosed with fundus albipunctatus (P59, P60) were compound heterozygotes for missense variants, one of which (c.982C>T) was previously reported in a patient with the same diagnosis.…”
Section: Resultssupporting
confidence: 85%
“…Although the latter was previously described as a hypomorphic allele, associated with low but substantial levels of both RPE65 and 11-cis-retinal in a murine model, 75 we observed a severe phenotype in two unrelated patients (P5 and P19) homozygous for this variant, who had a clinical diagnosis of LCA, nystagmus, keratoconus, light perception, and nondetectable ERG at the study baseline (at 32 and 43 years, respectively). Their clinical presentation was quite similar to the three siblings, homozygous for the same variant, recently described by Magliyah et al, 22 who reported nystagmus and nondetectable ERG in all the siblings and light perception in two patients (at the age of 32 and 36 years), whereas the third cases had a slightly better visual acuity (20/100 at 34 years). Finally, the two patients diagnosed with fundus albipunctatus (P59, P60) were compound heterozygotes for missense variants, one of which (c.982C>T) was previously reported in a patient with the same diagnosis.…”
Section: Resultssupporting
confidence: 85%
“…This is in contrast to patients with RPE65 ‐retinopathy, who almost always have non‐recordable ERG and a moderate‐to‐severe visual acuity reduction (Magliyah et al. 2020). Both patients had a general reduction in fundus autofluorescence, in keeping with a reduction in the turnover of retinoids due to inhibition of the visual cycle.…”
Section: Resultsmentioning
confidence: 82%
“…2011), (ii) the preserved visual acuity which is in contrast to the moderately or even severely reduced visual acuity in RPE65 ‐retinopathy and (iii) a relatively preserved ERG, which is almost always non‐recordable in RP‐like RPE65 ‐retinopathy (Magliyah et al. 2020). It was suggested that certain hypomorphic mutations such as mild missense mutations in RPE65 may lead to fundus albipunctatus rather than a more severe progressive retinopathy, by allowing for some residual enzyme activity (Hull et al.…”
Section: Discussionmentioning
confidence: 99%
“…The proportions of RPE65 -IRD in the EU-5 counties and the European region ranged between 1.2% in the UK and 14% in Germany [ 83 , 91 ]. Lastly, RPE65 mutations were estimated at ~ 1% in the US, while for the Middle East region, it varied between 4.81% in Saudi Arabia and 8% in Iran’s clinically diagnosed cases with IRD [ 81 , 85 , 87 , 89 ]. Also, based on the available data, the proportions of RPE65 in molecularly diagnosed cases with IRD was reported at 1.78% in China, 2.82% in the United Arab Emirates (UAE) and 4% in Brazil [ 57 , 84 , 92 ] (Supplementary Table B).…”
Section: Resultsmentioning
confidence: 99%
“…This proportion increased to 6.32% for the molecularly diagnosed 95 patients with RP and LCA [56]. 85,87,89]. Also, based on the available data, the proportions of RPE65 in molecularly diagnosed cases with IRD was reported at 1.78% in China, 2.82% in the United Arab Emirates (UAE) and 4% in Brazil [57,84,92] (Supplementary Table B).…”
Section: Proportion Of Rpe65-mediated Rp and Lca Combinedmentioning
confidence: 97%